A prescrição proscrita? Linguística e gramática no ensino de língua portuguesa - SILVA JÚNIOR, Francisco Ribeiro (2019)
This dissertation deals with the teaching of mother tongue, aiming at sketching an overview of the state of theoretical-methodological discussions about Portuguese language teaching in Brazilian Basic Education. To do so, we used as a methodological procedure the bibliographic research of the most accomplished authors in the field of language sciences, especially those who deal with Portuguese language teaching in Brazil. For decades, especially since the introduction of Linguistics in the curricula of the Brazilian Letras courses, the first publications on the subject have appeared, highlighting the central issue addressed in this text, which is the motto of the present investigation: the centrality of grammar in the teaching of Portuguese in Basic Education as opposed to a teaching based on the assumptions of the language sciences, especially Sociolinguistics, Textual Linguistics and Discursive and Textual Genres Theory. The authors studied occupy diverse and sometimes antagonistic positions on the pertinence of teaching explicit grammar in schools, considering the eminently normative character, the incoherences and theoretical inconsistencies that, in general, it presents. With the great discussions about the subject, a proposal of linguistic education has been outlined that contemplates assumptions of several fields of linguistic study, to the detriment of purely grammatical teaching. The current discussions on Portuguese language teaching in Brazil have pointed to the need for and urgency of a paradigm shift in the teaching of mother tongue that broadens the student's previous linguistic knowledge and therefore their linguistic competence through not only the teaching of grammar, but also, along with it, the wide diversity of aspects that the language presents.